(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Maḥmūd Zamakhsharī is a great mufassir, mutakallim, jurist who came from Movarounnahr. When the scientific, cultural and economic situation in Mā Warāʾ al-Nahr was in decline, Maḥmūd Zamakhsharī served to revive and restore science with selfless scientists. Ten of his works are known today, and scientific researches on these works continue without stopping.